Production and characteristics of the exocellular polysaccharide of a mutant Mycobacterium strain - Konícek, J; Daraselia, G Y; Konícková-Radochová, M; Lasík, J; Wurst, M; Koza, T (Folia microbiologica, 1990)
Mutant strains of Mycobacterium sp. V-649 producing highly mucous colonies on a solid cultivation medium were prepared after treatment with N-methyl-N'-nitro-N-nitrosoguanidine and production of the exocellular polysaccharide was tested. The strains were cultivated in media with suitable sugar sources under submerged conditions. It was found that Mycobacterium sp. V-649/15 produces a maximum of 15-19% polymer after a 5-6-d cultivation. Gas chromatography indicated that the exocellular polysaccharide produced by this strain is of glucan type.
Keywords: kultivační média; bakteriální polysacharidy; mutace; Mycobacterium; Polysaccharides, Bacterial; Chromatography, Gas; Mutation; chromatografie plynová; Culture Media